Pengaruh Store Atmosphere Dan Price Discount Terhadap Impulse Buying Dengan Positive Emotion Sebagai Variabel Intervening Pada Produk Fashion - Mir’atil Isnaini; Rose Rahmidani (Jurnal Ecogen, 2021)
The purpose of researche is to know the effect of store atmosphere and price discount on impulse buying with intervening variable is positive emotion of fashion product (study on consumer Ramayana Plaza Andalas Padang city). This research used causative form, the population in this research were society of Padang. The sample of this research as many 100 respondents that choose by using purposive sampling technic with consideration consumer impulse buying fashion product in Ramayana Plaza Andalas. It used primary data that obtained through distributing questionnaires to people in Padang with particular criteria. Analysis method was used is path analysis with SPSS 16. The result of this research shows (1) store atmosphere has significant effect and positif on impulse buying, (2) price discount has significant effect and positif on impulse buying, (3) store atmosphere has significant effect and positif on positive emotion,(4) price discount has significant effect and positif on positive emotion,(5) impulse buying has significant effect and positif on positive emotion,  (6) store atmosphere has significant effect and positif to impulse buying with variable intervening as positive emotion (7) price discount has significant effect and positif to impulse buying with variable intervening as positive emotion. Keywords: store atmosphere, price discount, impulse buying, positive emotion